2020
DOI: 10.1002/suco.201900338
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale fracture analysis of recycled aggregate concrete based on digital image processing technique

Abstract: Since recycled aggregate concrete (RAC) is valuable for green concrete and global sustainability, it has attracted many numerical research studies as a five‐phase material in mesolevel. In this study, the digital image processing (DIP) technique is used to obtain the real aggregate and mortar distribution of recycled concrete specimens. By applying the DIP MATLAB model, the real mesoheterogeneity of RAC is well represented. Based on the base force element method (BFEM), a mesomechanical model is constructed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…The aggregate grading was adjusted to obtain RAC with mechanical properties similar to those of NAC. Peng et al 41 conducted a mesoscale fracture analysis of RAC utilizing the digital image processing technique. The stress-strain curve, fracture energy and fracture distribution were analyzed and it was reported that the base force element method (BFEM) can be applied to study the failure mechanisms in heterogeneous materials, such as RAC.…”
Section: Introductionmentioning
confidence: 99%
“…The aggregate grading was adjusted to obtain RAC with mechanical properties similar to those of NAC. Peng et al 41 conducted a mesoscale fracture analysis of RAC utilizing the digital image processing technique. The stress-strain curve, fracture energy and fracture distribution were analyzed and it was reported that the base force element method (BFEM) can be applied to study the failure mechanisms in heterogeneous materials, such as RAC.…”
Section: Introductionmentioning
confidence: 99%
“…As shown recently 16 , damage in the early stages of of the prefailure regime mainly occurs away from the macrocrack path C . Similar stress redistributions around strain concentration sites have been observed to divert damage away from the crack path (viz., the crack tip) into the bulk of the sample 9,41 . Given that C essentially coincides with the energy bottleneck B(F E ) , this may initially seem counterintuitive given the close proximity to fracture of the bonds in B(F E ) .…”
Section: Resultsmentioning
confidence: 99%
“…Although only 2-3% of the Earth's landmasses, cities consume 60-80% of its energy, produce more than 75% of its greenhouse gases, and consume materials at a level that is projected to reach 90 billion tonnes by 2050 8 . These trends have seen a push for technologies that can harness disorder and heterogeneities in rational design and engineering of high performance and green materials 3,4,6,[9][10][11] . Great impetus for improvements in early detection of damage in materials and structures has also arisen, with the confluence of reduced cost and advances in nondestructive microstructural sensing technology, the rapid growth in construction and manufacturing activities, and the emergence of continuous structural health monitoring to meet government regulations on new and aging infrastructure 12,13 .…”
Section: List Of Symbols α(E)mentioning
confidence: 99%
“…An imagedependent approach can produce a realistic model by scanning an actual sample. However, it is a time-consuming and computationally expensive method and is highly dependent on image resolution [26][27][28][29][30][31][32]. These specifications limit the shape variations and number of models, which can be possibly produced.…”
Section: Introductionmentioning
confidence: 99%